Peran Perceived Value Dalam Memediasi Pengaruh E-Wom Terhadap Minat Beli Mahasiswa Generasi Z di Universitas Perjuangan Tasikmalaya (Shopee Case Study) - Ashari, Riki Aksan Aji; Huhamad Pauzy, Depy; Nafilah Faza, Shita; Nugraha, Helmi; Husni Herlisana Putra, Fajril (Jurnal Nasional Manajemen Pemasaran dan SDM, 2026)
This research aims to analyze the role of perceived value in mediating the effect of electronic word of mouth (e-WOM) on the purchase intention of Generation Z students who use Shopee at Universitas Perjuangan Tasikmalaya. This study employed a quantitative, survey-based approach. The sampling technique used was purposive sampling with a total of 100 respondents who had previously made purchases through Shopee. Data were collected using an online questionnaire measured with a five-point Likert scale. . The results indicate that e-WOM has a positive and significant effect on both perceived value and purchase intention. Furthermore, perceived value has a positive and significant effect on purchase intention and partially mediates the relationship between e-WOM and purchase intention. These findings suggest that user-generated content, such as reviews and recommendations on the Shopee platform, enhances consumers’ perceived value, thereby increasing their purchase intention.